A Novel Workflow for Non-Animal PBK Modelling of UV Filters: Oxybenzone as a Case Study - Golbamaki, Nazanin; Moustié, Anne; Hewitt, Nicola J.; Lereaux, Guillaume; Burbank, Matthew; Ben Yahya, El Mehdi; Grégoire, Sébastien; Roussel-Berlier, Laurène (Pharmaceuticals (Basel, Switzerland), 2025)
Background/Objectives: Physiologically based kinetics (PBK) modelling provides (internal) exposure concentrations. We used a PBK model parameterized exclusively with in silico and in vitro data in a bottom-up approach to predict the pharmacokinetics of oxybenzone, a UV filter, present in two formulations (for which dose-normalized Cmax and AUC from clinical studies were different). Methods: Skin absorption data were used to refine chemical-specific dermal absorption parameters for oxybenzone in a lotion and spray. The Transdermal Compartmental Absorption and Transit (TCAT) model in GastroPlus® 9.9 was used to estimate vehicle and skin layer diffusion and partitioning and then used to simulate systemic exposure. The model was validated according to the OECD 331 guideline. Results: PK profiles simulated for both formulations after single and repeated applications correlated with clinical data profiles (used only to validate our approach), with a deviation from the Cmax and AUC of <2-fold. Sensitivity and uncertainty analyses indicated that most input parameters had a medium to high reliability, whereas only a few parameters related to dermal delivery had a low reliability: the partition coefficient between vehicle and water for spray and the diffusion coefficient in stratum corneum for lotion. In vitro skin absorption results suggested that absorption kinetics were not statistically different between the formulations; however, parameters such as vehicle evaporation time were different. The fine-tuned TCAT model containing the absorption data suggested that the variability in clinical data might be due to other factors, e.g., the small number of subjects. Conclusions: These results demonstrate how formulation-dependent absorption kinetics improve confidence in estimated exposure, thanks to the PBK model with its bottom-up approach for nonanimal-based safety assessments.